Performance and genetic variation in a provenance test of Araucaria cunninghamii - Santos, Wanderley dos; Aguiar, Ananda Virginia de; Souza, Bruno Marchetti de; Araujo, Daniela; Machado, Celso; Moraes, Mário Luiz Texeira de; Sebbenn, Alexandre Magno; Freitas, Miguel Luiz Menezes (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to assess the genetic variability of Araucaria cunninghamii in a provenance test and to estimate the genetic gains in its wood production, based on different selection intensities. The trial was established in Luís Antônio, in the state of São Paulo, Brazil, using open-pollinated seed from Queensland, Australia. The experimental design used was a randomized complete block with six replicates, and four plants per plot. Diameter at breast height (DBH), stem form, and survival were measured at 29 years after planting. Significant differences were detected among provenances. The coefficient of genotypic variation between provenances was high (60%) for DBH and stem form. The mean values for DBH and stem form were 23.21 cm and 4.50, respectively. The provenances Langkelly Creek, Brooweena L.A., Yarraman, and St. Agnes showed the best performance for DBH, and Imbil Seed Orchard, Brooweena L.A, St. Agnes, St. John, and Yarraman, for stem form. Genetic gains ranged from 0.5 to 24.8% for DBH, and from 0.9 to 3.5% for stem form.